محاكاة أداء التنضيد بتقسيم التردد المتعامد OFDM باستخدام MATLAB - الرضوان, هيثم (Latakia University Journal -Engineering Sciences Series, 2017)
يهدف البحث إلى دراسة أداء تقنية التنضيد بالتقسيم الترددي المتعامد OFDM ، التي تستخدم في شبكات الجيل الرابع وما بعده وشبكات WiFi. استخدمت في الدراسة المحاكاة باستخدام MATLAB ،مع الأخذ بالحسبان عدد الحوامل الفرعية والتباعد بين الحوامل وعرض الحزمة، والتداخل البيني بين الرموز ، والبادئة الدورية، ونسبة الإشارة إلى الضجيج في نظام OFDM. تطلب ذلك إجراء دراسة تحليلية لمستقبل ومرسل OFDM والتعديل متعدد الحوامل لتحديد القيم الأنسب لبارامترات اللازمة كدخل لإجرا ء المحاكاة البرمجية.The work aims to study the performance of Orthogonal Frequency Division Multiplexing OFDM technique, which is applied in the fourth generation mobile networks and beyond and WiFi. Used in the study simulation using MATLAB, taking into account the number of sub-pregnant Carriers, and the spacing between carriers and bandwidth, and Cyclic Prefix, and Inter-Symbol Interference and the proportion of the ratio of signal-to-noise in OFDM system. This required an analytical study of the future of the sender and the receiver OFDM multi-carrier modulation to determine the most appropriate values for the parameters of the necessary income to conducted at the simulation.